RELIGIOUS MODERATION IN ISLAMIC EDUCATION LEARNING TO COUNTER RADICALISM: Study at SMAN 1 Sugihwaras Bojonegoro - Smeer, Zeid B.; Rosyidah, Inayatur (ULUL ALBAB Jurnal Studi Islam, 2021)
Among the negative impacts of advances in digital technology is the spread of false information based on religion which plays a role in shaping young people to become radicalized and justifying violence for religious solidarity. Efforts should be made to internalize the values of religious moderation in Islamic Education learning (PAI) in schools, so that students are able to understand, live and practice moderate Islamic values according to the Islamic vision, namely Islam Raá¸¥mat li al-Ã‚lamÃ®n. This research is a descriptive qualitative research with the object of research at SMAN 1 Sugihwaras Bojonegoro. Data obtained through interviews, documentation, and observation. The data analysis technique used Miles and Huberman's model in the form of data reduction, data display, and conclusion drawing. The data validity used triangulation technique. The findings show that the internalization of religious moderation in Islamic education learning to counter radicalism can be started by determining educational policies and objectives, as well as through the design of a the prescribed/intended curriculum and a hidden curriculum. Meanwhile, the contribution of religious moderation in general is to mature students' intellectual, mental and social skills as multicultural social beings with respect for diversity and a willingness to cooperate fairly with anyone.